Eksplorasi Jamur-Jamur yang Berasosiasi dengan Penyakit Mati Meranting pada Tanaman Kakao di Kota Padang - Nurbailis Nurbailis; Rummah Yulisyah; Novri Nelly (Jurnal Proteksi Tanaman, 2021)
Branch dieback is one of the primary diseases in cacao plants. The disease affects young shoots and twigs, causes leaves to die, and leaves them bare, interfering with photosynthesis. This study aimed to determine the causative pathogens in Padang City. The locations were: Sungai Sarik Kuranji, Lubuk Minturun Koto Tangah, and Teluk Kabung Bungus. The locations have the following criteria: age ? three years, the number of plants at the location ? 50 individuals, and found symptoms of branch dieback. The research used descriptive methods. The sample represented 10% of the total number of plants at the location, was collected randomly. The results found four species of fungi associated with the disease, namely Oncobasidium theobromae, Botrydiplodia theobromae, Fusarium decemcellulare, and Fusarium sp1.